O futuro do presente - Corso, Diana Lichtenstein; Corso, Mário; Bigliani, Lea B. Nuss de; Bigliani, Guillermo; Getlinger, Patricia Vianna; Coelho Junior, Nelson (Percurso, 2011)
Realização: Gisela Haddad, Vera Zimmermann, Cristiane Curi Abud.